MATHEMATICAL MODELING OF A DOUBLE PASS UNDERFLOOR HEATING SYSTEM - Beithou, Nabil (European Scientific Journal, ESJ, 2014)
Toward a green building construction, the underfloor heating by solar energy in multi-apartments buildings was considered. A system of double pass underfloor heating with evacuated tube solar collector was modeled. The used energy is a renewable energy that does not affect the environment. The system modeled consist of an evacuated tube solar collector for heating the water, the underfloor heating system consist of two lined up pipes to help in the case of low inlet water temperatures, the control unit used to manage the heating system and save energy in case of excess solar radiation. The governing equations for the system based on energy conservation were written and simulated iteratively. It has been found that at low temperatures the required mass flow rate of hot water increases dramatically, as a result of insufficient heat to cover the heating load of the space, this system allow the double pass heat transfer mode to be switched on to reduce the flow velocity and allow the workability of the system to be valid at a lower temperatures. Also in the case of low heating loads, the amount of hot water required to cover the heat requirement of the space will be very low. The reduction in the heating load will allow the system to send a part of the hot fluid to the storage tank to store the hot water and achieve a lower temperature water flow. The simulation of such model could give a clear idea about the workability of the underfloor heating system, the required solar collector area, and manage the energy within the system. A more detail analyses of the DPUFHS is the topic of a current study. The underfloor is considered with multi-pass arrangement, and the control unit will simulate transient conditions of the system. A more realistic system will be considered by accounting for the floor heat losses and the thermal storage in the walls and floor.